Pomiędzy queerową subwersją a „middle-class mainstreaming”. O twórczości drag queen Mony Lizak - Magdalena Stoch (Literatura i Kultura Popularna)
This article is a critical reflection on the stage and musical work of drag queen Mona Lizak. The author asks about the form (stage style) and content (ideological message) of the artist’s conceptual and speculative works and its connections with the tradition of queer performance. The article presents the historical and cultural contexts of drag, from amateur underground theatres to the contemporary commercialized queer scene, and emphasizes how Mona Lizak’s work reflects the tensions between subversive ideology and mainstream trends. Particular attention is paid to the artist’s political message, which criticises the exclusion of LGBT+ persons, the dominance of the Catholic church, and social issues such as the climate crisis and women’s rights. The article also explores the aesthetics of camp, the performativity of gender, and the significance of queer ‘monstrosity’ as a form of resistance to hegemonic social norms. Mona Lizak’s work is also analyzed through categories such as camp, carnival, monstrosity, freek show and rape culture. Ultimately, Mona Lizak’s work is treated as a lens that focuses key discourses of the LGBT+ community, as well as an example of the dynamic interaction between counterculture and capitalist appropriation of queer performance, highlighting her unique place on the Polish drag scene.